Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1161/hypertensionaha.113.01452
|View full text |Cite
|
Sign up to set email alerts
|

Renal Sympathetic Denervation in Patients With Treatment-Resistant Hypertension After Witnessed Intake of Medication Before Qualifying Ambulatory Blood Pressure

Abstract: A pproximately 10% of patients treated for hypertension remain with uncontrolled high blood pressure (BP), despite prescription of antihypertensive drugs.1 Renal sympathetic denervation has been introduced as a new treatment of hypertension apparently resistant to drug treatment.2 However, it has been known for decades that poor drug adherence is a major problem among these patients. 3,4 It is unknown to what degree the decline in BP after renal denervation (RDN) 2 is caused by denervation itself or concomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 18 publications
3
75
0
5
Order By: Relevance
“…A third reason may be because of the variation in the blood pressure response to renal denervation. The responder rates (a decrease in systolic blood pressure of ≥10 mm Hg) were only 33% and 50%, respectively, in the reports from Fadl Elmula et al 2 and Hart et al, 3 and these values were lower than those in the Symplicity HTN-1 study. These studies highlight that a big variation in the response of blood pressure to renal denervation exists, and that in some patients blood pressure may increase.…”
Section: To the Editormentioning
confidence: 73%
See 1 more Smart Citation
“…A third reason may be because of the variation in the blood pressure response to renal denervation. The responder rates (a decrease in systolic blood pressure of ≥10 mm Hg) were only 33% and 50%, respectively, in the reports from Fadl Elmula et al 2 and Hart et al, 3 and these values were lower than those in the Symplicity HTN-1 study. These studies highlight that a big variation in the response of blood pressure to renal denervation exists, and that in some patients blood pressure may increase.…”
Section: To the Editormentioning
confidence: 73%
“…However, it did not cite other studies that did not observe a decrease in blood pressure after renal denervation. For example, Fadl Elmula et al 2 and Hart et al 3 separately reported that renal denervation did not decrease office systolic blood pressure. In addition, some studies, for example, the report of Witkowski et al, 4 showed that renal denervation did not decrease ambulatory blood pressure.…”
Section: To the Editormentioning
confidence: 99%
“…I Norge er det nylig startet en studie med renal denervering ved Universitetssykehuset Nord-Norge i Tromsø (17) og en annen ved Oslo universitetssykehus, Ullevål -«Oslo RDN Study» (NCT 01673516) (18). I Oslostudien randomiseres pasientene til renal denervering eller spesialtilpasset medikamentell behandling etter undersøkelse med impedanskardiografi (19).…”
Section: Diskusjonunclassified
“…Den første åpne fasen av Oslo RDN Study er publisert (18). Den viser usikker effekt på blodtrykket hos pasienter med dokumentert behandlingsresistent hypertensjon.…”
Section: Figur 2 Ablasjonskateter I Nyrearterie Nervene Er Skjematisunclassified
See 1 more Smart Citation